MicroRNAs Encoded by Bovine Leukemia Virus (BLV) Are Associated with Reduced Expression of B Cell Transcriptional Regulators in Dairy Cattle Naturally Infected with BLV - Frie, Meredith C.; Droscha, Casey J.; Greenlick, Ashley E.; Coussens, Paul M. (Frontiers in Veterinary Science, 2018)
Bovine leukemia virus (BLV) is estimated to infect over 83% of dairy herds and over 40% of all dairy cows in the United States. While BLV only causes leukemia in a small proportion of animals, research indicates that BLV+ cattle exhibit reduced milk production and longevity that is distinct from lymphoma development. It is hypothesized that BLV negatively affects production by interfering with cattle immunity and increasing the risk of secondary infections. In particular, BLV+ cows demonstrate reduced circulating levels of both antigen-specific and total IgM. This study investigated possible mechanisms by which BLV could interfere with the production of IgM in naturally infected cattle. Specifically, total plasma IgM and the expression of genes IGJ, BLIMP1, BCL6 and PAX5 in circulating IgM+ B cells were measured in 15 naturally-infected BLV+ and 15 BLV- cows. In addition, BLV proviral load (a relative measurement of BLV provirus integrated into host DNA) and the relative expression of BLV TAX and 5 BLV microRNAs were characterized and correlated to the expression of selected endogenous genes. BLV+ cows exhibited lower total plasma IgM and lower expression of IGJ, BLIMP1 and BCL6. While BLV TAX and BLV miRNAs failed to correlate with IGJ expression, both BLV TAX and BLV miRNAs exhibited negative associations with BLIMP1 and BCL6 gene expression. The results suggest a possible transcriptional pathway by which BLV interferes with IgM production in naturally infected cattle.